Measuring the Other Half: New Measures of Intangible Investment from the ONS. (August 2019) - Martin, Josh
Only half of investment by firms is in physical capital, such as buildings and machinery. The other half is in intangible assets, such as branding, software and training. This has been true for the past two decades or more in the UK, but only if you step beyond the measures in the National Accounts, which include only some of the recognised intangible assets. This paper surveys ongoing work at the Office for National Statistics to develop measures of investment in intangible assets, using new insights and innovative approaches. In particular, this paper reviews developments in three areas: in-house branding investments, employer-funded training investments, and in-house investments in organisational capital. We reconsider some of the key assumptions made in the literature and propose alternative approaches to measurement. The paper concludes by considering implications of this work, and identifies some of the remaining gaps in the evidence base for measuring intangible assets.